THREE CANDIDATE GENES AND ITS ASSOCIATION WITH QUANTITATIVE VARIATION OF EGG PRODUCTION TRAITES OF LOCAL QUAIL BY USING PCR-RFLP - & AL-Barzinji, Ahmed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The aim of study was to investigate the potential candidate gene SEMA3E, TLX and GH and their association with the economic traits, which is becoming increasingly important in poultry breeding program. A total of 72 genomic DNA samples from three female local lines of quail including (desert, brown and white) were collected to determine the association of genes with reproduction trait using PCR-RFLP Technique. According to growth performance the Best Linear Unbiased Prediction (BLUP) value in selected females for high (H) and low (L) production traits was ranged from -9.2173 to 0.3827. This value is used to estimate body weight at first egg (BWFE), age at first egg (AFE), weight at first egg (WFE), Egg number per Bird (ENPH), Average egg weight (EWTA), and hen day (HD) in three lines. The results indicate that there was a wide intra specific SEMA3E, TLX and GH variability among these local quails which identifying twelve differences genotypes. The identified genotypes for all genes had a significantly (P<0.05) affected on the reproduction trait during first 150 days. The quail’s genotype AAABAA always exhibited the largest body weight at first egg in desert H line, while L line of white was greater in Egg number per bird and hen day of the genotype ACCCAC. No significant associations were observed between all loci and age at first egg trait among local quails. The results indicate that there are agreements between BLUP values with PCR-RFLP results to achieve a favorable selection response in reproductive performance of local quail in Kurdistan region, Iraqi.